EVALUATION OF QUALITY ORGANIZATION AND SAFETY AT WORKPLACE (Municipal economy of cities. Series: «Economy science», 2016)
The problem of evaluation of quality organization and safety at workplace considered, identified shortcomings. Among the existing methods and techniques of evaluation selected those that have the greatest informative value and can form the basis for further work. Proposed as a basic system to use an ergonomic evaluation of the "human-technics-environment" and improve it through the use of elements of the Elmer’s system and Fine-Kinney method. The combination of these components allowed to expand the list of explore characteristics of the workplace and estimated their impact on human safety at the workplace during of working process. The result is an improvement evaluation of quality organization and safety at workplace. This system held practical testing, which gave positive results. Key words: safety, employee, workplace, professional risk, ergonomic evaluation, Elmer’s system, Fine-Kinney method.